INTERNATIONAL EXPERIENCE AND COMPARATIVE ANALYSIS OF ALTERNATIVE DISPUTE RESOLUTION METHODS - С.Э. Асанова; Ф.С. Карагусов; А.А. Нукушева; А.К. Джангабулова; Т.Э. Воронова (Хабаршы. Заң сериясы)
This article is devoted to the scientific study of international legal regulation of such phenomena as mediation through the analysis of the legislation of foreign countries and the national law of the Republic of Kazakhstan. This article presents various points of view of foreign, Russian, and domestic scientists on dispute resolution in the mediation procedure. From a scientific perspective, legal features of dispute resolution in the order of mediation are of particular interest in connection with the relatively new and unexamined phenomenon of modernity, arising from increasing processes of globalization and internationalization of legal systems as well as scientific and technical progress. Particular attention is paid to the analysis of the experience of various countries in mediation, including the USA, Germany, Austria, India, and China, which allows us to identify common principles and features of the application of mediation in different legal systems. The experience of the Republic of Kazakhstan in the development of the institution of mediation, its legislative regulation and prospects for further integration within the EAEU are also considered.